The Determinants of Inflation in the Kenyan Economy - Ochieng, Osborn; Mukras, Prof. M. S.; Momanyi, Dr. Gideon (International Journal of Economics, 2016)
Purpose: In many Sub-Saharan countries it is challenging for monetary authorities to control inflation even if there is a political will, due to weak institutional frameworks, thin financial markets and imperfect competition among banks.The purpose of this study therefore was to investigate the determinants of inflation in the Kenyan economy. Methodology:An explanatory research design was adopted.The study was carried out in Kenya,an East African country. The study used data from secondary sources only.The study employed an empirical test of the relation between inflation and the determining factors Results:These results imply that Price fluctuations and Lag inflation rates greatly affect inflation rate positively while real GDP growth affects inflation rate negatively.The findings also showed that Money supply growth, Foreign Exchange rate and interest rate do not have a significant relationship with inflation. In addition the findings revealed that the inflation model exhibits a linear structure as the coefficients of squared terms of the predictor variables were found to be statistically insignificant. Based on the findings above the study concluded that real GDP growth, price fluctuations (changes in oil prices) and the previous period's inflation rate (lag inflation rate) are the ideal factors that affect inflation in Kenya. Recommendations:Unique contribution to theory, practice and policy .Several recommendations and policy implications emanate from the study. Firstly, Real GDP growth is the main instrument policy makers should aim at in controlling the inflation rate. According to the results, real GDP growth is a significant determinant of inflation rate during the study period. An increase in real GDP leads to a decrease in inflation rate.